The use of McConnell taping to correct abnormal biomechanics and muscle activation patterns in subjects with anterior knee pain: a systematic review - Louw, Quinette A; Leibbrandt, Dominique C (Journal of Physical Therapy Science, 2015)
[Purpose] The aim of this review was to present the available evidence for the effect of McConnell taping on knee biomechanics in individuals with anterior knee pain. [Methods] The PubMed, Medline, Cinahl, SPORTDiscus, PEDro and ScienceDirect electronic databases were searched from inception until September 2014. Experimental research on knee biomechanical or EMG outcomes of McConnell taping compared with no tape or placebo tape were included. Two reviewers completed the searches, selected the full text articles, and assessed the risk of bias of eligible studies. Authors were contacted for missing data. [Results] Eight heterogeneous studies with a total sample of 220 were included in this review. All of the studies had a moderate to low risk of bias. Pooling of data was possible for three outcomes: average knee extensor moment, average VMO/VL ratio and average VMO-VL onset timing. None of these outcomes revealed significant differences. [Conclusion] The evidence is currently insufficient to justify routine use of the McConnell taping technique in the treatment of anterior knee pain. There is a need for more evidence on the aetiological pathways of anterior knee pain, level one evidence, and studies investigating other potential mechanisms of McConnell taping.